Questionnaire for a survey on forms of evaluation of research proposals oriented to the search for solutions to development problems : characteristics, processes and evaluation criteria - Consejo Latinoamericano de Ciencias Sociales - CLACSO (CLACSO, 2021)
We intend, through this questionnaire, to gather information on the forms of evaluation of research proposals oriented to the search for solutions to development problems, their characteristics, processes and evaluation criteria by specialists and/or authorities of scientific and/or higher education organizations in countries of the Global South, particularly in developing economies of South Asia like Bangladesh, India and Sri Lanka. In this way, we aim to highlight and analyze relevant and quality ways of evaluating research proposals for funding to better adapt to the United Nations Sustainable Development Goals (SDGs), global "grand challenges" and local critical situations, as well as to facilitate funding schemes that promote more inclusive research systems.